Auditory psychophysical analysis of healthy individuals based on audiometry and absolute threshold tests - H. S, Sanjay; S, Bhargavi; S, Madhuri (International Journal of Engineering and Technology, 2018)
Psychophysics is one of the most important aspects to assess the auditory behavior in human beings. The present study has been successful in exploring the temporal resolution with respect to auditory stimulus thereby helping in the analysis of the auditory psychophysics in human beings which has been gaining wide acceptance in behavioral research. This research work concentrated on subjects with no known auditory pathological history, both males and females of different age groups, subjects exposed to noise (fabrication industry, chemical industry) and professional basketball players. The subjects were made to undergo conventional Audiometry Test (AT) as well as the Absolute Threshold Test (ATT) developed. A similar pattern was observed in the results of AT across all types of subjects. There were no eminent variations observed other than a characteristic dip between 4000 – 6000 Hz. Hence it was concluded that the AT cannot assess the variations in hearing perception for normal individuals with respect to age, sex and occupational exposure. The Absolute Threshold (ATTh) obtained from the ATT were found to be varying in subjects with respect to age and sex wherein the males had a better ATTh than females. Also ATTh was found to deteriorate with age. ATTh was able to differentiate the hearing perception of the positively conditioned (basketball players) and negatively conditioned (chemical and fabrication industry) subjects thereby proving to be an efficient tool to assess the hearing perception in the conditioned and the control set of subjects. Hence ATT based approach could be very useful in sports training and rehabilitation approaches and hence can be a very useful tool in the assessment of auditory temporal resolution of human beings in various applications.